A 14-Year Follow-Up Study of Sequelae in Primary Teeth and Permanent Successors After Dental Trauma - Costa, Mariana Pires da (2023)
Objective: To evaluate the presence of sequelae in primary teeth and their permanent successors, as well as associations between TDI and the presence of sequelae in both teeth. Material and Methods: In this 14-year retrospective study, 2.290 records were reviewed, 192 patients who suffered dental trauma in primary teeth were followed until the eruption of successor teeth were included. Descriptive, chi-square, and regression logistic with generalized estimating equations tests were performed (p<0.05). Results: 362 primary and successor teeth were followed. Sequelae were present in 71.8% of primary teeth and 25.7% of their successors. Teeth with complicated fracture (100%), extrusion (100%) and avulsion (100%) resulted in the largest amounts of sequelae in primary teeth and intrusion (61%) on their successors. Age was associated with sequelae in permanent teeth (p<0.01). Extrusion (OR 10.06; CI 2.12-47.63) and intrusion (OR 7.51; CI 2.73-20.70) had a higher risk to cause sequelae in primary and permanent teeth, respectively. Conclusion: The type of injury involved influenced the sequelae in traumatized teeth and their successors, and the age of the child influenced the presence of sequelae in permanent teeth.